Relationships between systemic sclerosis and atherosclerosis: screening for mitochondria-related biomarkers - Wang, Fei; Lyu, Xiao Yan; Qin, Yi Ming; Xie, Mei Juan (Frontiers in Genetics, 2024)
Background: Patients with systemic sclerosis (SSc) have a high incidence of atherosclerosis (AS). Mitochondrial injury in SSc can cause endothelial dysfunction, leading to AS. Mitochondria appear to be hubs that link SSc to AS. This study aimed to identify the mitochondria-related biomarkers of SSc and AS.We downloaded the SSc (GSE58095) and AS (GSE100927) datasets from the Gene Expression Omnibus (GEO) database. Then, we identified common differentially expressed genes (DEGs). After taking the intersection between genes with identical expression trends and mitochondrial genes, we used the least absolute shrinkage and selection operator (LASSO) and random forest (RF) algorithms to identify four mitochondria-related hub genes. Diagnostic nomograms were constructed to predict the likelihood of SSc and AS. We used the CIBERSORT algorithm to evaluate immune infiltration in both disorders. We predicted the transcription factors for hub genes and validated them using two datasets.Results: In total, 112 genes and 13 mitochondria-related genes were identified. These genes were significantly enriched for macrophage differentiation, collagen-containing extracellular matrix, collagen binding, antigen processing and presentation, leukocyte transendothelial migration and apoptosis. Four mitochondria-related hub DEGs (IFI6, FSCN1, GAL, and SGCA) were identified. The nomogram showed good diagnostic values for GSE58095 (AUC = 0.903) and GSE100927 (AUC = 0.904). Memory B cells, γδT cells, Mo Macrophages, and activated mast cells were significantly increased in AS. Resting memory CD4+ T cells was decreased and M1 macrophages were increased in the SSc. They were closely linked to multiple immune cells. Gene set enrichment analysis (GSEA) showed that IFI6 and FSCN1 are involved in immune-related pathways in AS and SSc. GAL and SGCA are related to mitochondrial metabolism pathways in SSc and AS. Twenty transcription factors (TFs) were predicted. Two transcription factors, BRCA1 and PPARγ, were highly expressed in SSc and AS. Conclusions: Four mitochondria-related biomarkers were identified in both SSc and AS. They have a high diagnostic value and are associated with immune cell infiltration in both disorders. This study provides new insights into the pathological mechanisms underlying SSc and AS. The genes' specific roles and mechanisms of action require further clinical validation in SSc patients with AS.